Forage Production of Grass–Legume Binary Mixtures on Intermountain Western USA Irrigated Pastures. Issue 3 (16th June 2017) - Cox, Steven; Peel, Michael D.; Creech, J. Earl; Waldron, Blair L.; Eun, Jong‐Su; Zobell, Dale R.; Miller, Rhonda L.; Snyder, Don L.
Abstract : Well‐managed irrigated pasture production can be optimized without nitrogen (N) fertilizer. The objective was to determine mixture and planting ratios of tall fescue ( Schedonorus arundinacea Schreb.) (TF), meadow brome ( Bromus riparius Rehm.) (MB), orchardgrass ( Dactylis glomerata L.) (OG), timothy ( Phleum pratense L.) (TIM), and perennial ryegrass ( Lolium perenne L.) (PRG) with alfalfa ( Medicago sativa L.) (ALF), birdsfoot trefoil ( Lotus corniculatus L.) (BFTF), or cicer milkvetch ( Astragalus cicer L.) (CMV) that maximize productivity. Planting ratios were 0:100 (grass:legume), 25:75, 50:50, 75:25, and three 100:0 grass monocultures fertilized at 0, 67, and 134 kg N ha −1 . Seasonal production of TF–ALF was 12.69 Mg ha −1, equal to TF fertilized at 134 kg N ha −1 . ALF mixtures with MB, OG, TIM, and PRG produced 12.57, 10.97, 11.77, and 10.74 Mg ha −1, respectively, and 8 to 40% more than grasses receiving 134 kg N ha −1 . Production of BFTF mixtures with TF, MB, and OG were 11.69, 11.45, and 9.95 Mg ha −1, respectively, equal to their respective grass monoculture receiving 134 kg N ha −1 . The BFTF–TIM and BFTF–PRG mixtures averaged 12% more forage than grass monocultures receiving 134 kg N ha −1 . Production of CMV‐grass was similar to that of grasses receiving 67 kg N ha −1 . Seasonal forage distribution was more uniform in ALF– and BFTF–grass mixtures, averaging 30% more at the second and third harvests than fertilized grasses. The TF and MB legume mixtures averaged 7% more production in the 50:50 planting ratios than the other two grass–legume mixtures, while the 50:50 and 25:75 ratios of OG and TIM–legume mixtures averaged 12% more than the 75:25 and the 25:75 PRG–legume planting ratio averaged 9% more than the 50:50 and 75:25. Forage production of grass–legume mixtures can equal or exceed fertilized grass monocultures and with more uniform distribution over the growing season.